Effects of low humidity on comfort, health, and indoor environmental quality: literature review - Hamehkasi, Maryam (Kansas State University, 2016)
This study was conducted to investigate the effects of humidity on comfort, health, and indoor environment quality (IEQ) using a comprehensive literature review. Published papers were obtained from keyword and citation searches from bibliographic databases (i.e., PubMed, Scopus, and Google Scholar), including papers from 1985 to 2015. Over 600 papers were identified and classified based on topic area; from these papers, seven were chosen as case studies for this report. The seven papers represent studies on various topics, including bacteria, influenza/virus transmission, elderly subjects, indoor air quality, effects on eyes and skin, dust mites, and asthma. Theunissen et al. (1993) showed bacteria (gram positive and gram negative) do not act the same in low or high humidity conditions. Lowen et al. (2007) studied influenza transmission. Sunwoo et al. (2006) used elderly subjects to study eyes, skin, and comfort. Reinikianen et al. (1992) and Nordström et al. (1994) surveyed a large number of subjects, controlled humidity, and assessed multiple factors regarding indoor health and comfort. Arlian et al. (2001) implemented dehumidifier as a way to reduce house dust mites. Kaminsky et al. (1995) tested asthmatic subjects and healthy subjects to compare the effects of dry air on asthma. From these case studies low humidity appeared to have a variety of effects on health and comfort; however, no precise and defined borderline exists to distinguish acceptable low humidity. Acceptable low humidity levels depend on many factors, including building location and purpose, age of occupants, and climatic conditions.
Keywords: comfort; health; indoor environmentalLow humidity